Exploring the sense of privacy as barrier to formal health service among the elderly with constipation in Kelantan - Abdul Wahab, Patimah; Ali, Siti Hawa; Lee, Yeong Yeh; Abdul Kadir, Azidah; Mohd Yusoff, Dariah (2016)
Introduction: Chronic constipation is a common gastrointestinal disorder among the elderly. It has a significant negative impact on health related quality of life which is largely attributable to failure in managing the symptom. While constipation-related privacy issue has been identified in other population, there is limited research on such issue in Malaysia.